Cost analysis of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy and the risk factors for their increased cost in a public insurance health care system - Single centre study - Klos, Dušan; Riško, Juraj; Kriváčková, Dominika; Loveček, Martin; Skalický, Pavel; Neoral, Čestmír; Melichar, Bohuslav; Mohelníková-Duchoňová, Beatrice; Lemstrová, Radmila (European journal of surgical oncology, 2020)
INTRODUCTION: This study aimed to evaluate the costs of CRS and HIPEC and treatment of the related postoperative complications in the public healthcare system. We also aimed to identify the risk factors that increase the cost of CRS and HIPEC. MATERIALS AND METHODS: We retrospectively evaluated 80 patients who underwent CRS and HIPEC between February 2016 and November 2018 in the Department of Surgery, University Hospital of Olomouc, Czech Republic. Intraoperative factors and postoperative complications were assessed. The treatment cost included the surgery, hospital stay, intensive care unit (ICU) admission, pharmaceutical charges including medication, hospital supplies, pathology, imaging, and allied healthcare services. RESULTS: The postoperative morbidity rate was 50%, and the mortality rate was 2.5%. The mean length of hospitalisation and ICU admission was 15.44 ± 8.43 and 6.15 ± 4.12 for all 80 patients and 10.73 ± 2.93 and 3.73 ± 1.32, respectively, for 40 patients without complications, and 20.15 ± 13.93 and 8.58 ± 6.92, respectively, for 40 patients with complications. The total treatment cost reached €606,358, but the total reimbursement was €262,931; thus, the CRS and HIPEC profit margin was €-343,427. Multivariate analysis showed that blood loss ≥1.000 ml (p = 0.03) and grade I-V Clavien-Dindo complications (p < 0.001) were independently associated with increased costs. CONCLUSION: The Czech public health insurance system does not fully compensate for the costs of CRS and HIPEC. Hospital losses remain the main limiting factor for further improving these procedures. Furthermore, treatment costs increase with increasing severity of postoperative complications.
Keywords: Equipment and Supplies, Hospital; nádory apendixu; Appendiceal Neoplasms; Humans; Healthcare Financing; lidé středního věku; vybavení a zásoby nemocnice; financování vládou; Female; Aged; dospělí; nádory vaječníků; Ovarian Neoplasms; Costs and Cost Analysis; Hyperthermia, Induced; senioři; lidé; Cytoreduction Surgical Procedures; Postoperative complications; Diagnostic Imaging; indukovaná hypertermie; mortalita v nemocnicích; krvácení při operaci; náklady a analýza nákladů; Cost analysis; Pharmaceutical Services; Adult; Postoperative Complications; zdravotní pojištění; pooperační komplikace; cytoredukční chirurgie; ženské pohlaví; kolorektální nádory; Male; jednotky intenzivní péče; Middle Aged; Financing, Government; Czech Republic; farmaceutické služby; Intraperitoneal hyperthermic chemotherapy; Insurance, Health; Insurance, Health, Reimbursement; Intensive Care Units; Cytoreductive surgery; diagnostické zobrazování; úhrada zdravotního pojištění; Hospital Mortality; Česká republika; mužské pohlaví; peritoneální nádory; Length of Stay; Peritoneal Neoplasms; délka pobytu; Colorectal Neoplasms; Blood Loss, Surgical; financování zdravotní péče